Hubungan Career Adaptability dengan Work Readiness Mahasiswa Tingkat Akhir D3 di Universitas Negeri Padang - Ayuni, Sarah; Nio, Suci Rahma (Lembaga Yasin AlSys, 2025)
This study aims to examine the relationship between career adaptability and work readiness among final-year diploma (D3) students at Universitas Negeri Padang. A quantitative method with a correlational design was employed. The study population consisted of final-year D3 students from the 2021–2022 cohorts, with a sample of 311 participants selected using proportionate stratified random sampling. The instruments used included the Career Adapt-Abilities Scale (CAAS) and a work readiness scale. Data were analyzed using the Pearson product-moment correlation test. The analysis yielded a correlation coefficient of 0.603 with a significance value (2-tailed) of 0.000, indicating a positive and significant relationship between career adaptability and work readiness. This means that the higher a student’s level of career adaptability, the higher their level of work readiness, and vice versa. These findings underscore the crucial role of career adaptability in preparing students for the workforce and provide a foundation for strengthening career guidance interventions in vocational higher education settings.